THE STRATEGY FOR OPTIMIZING THE COLLECTION OF TRADE ZAKAT IN BANJAR CITY - Munandar, Eris; Nopianti, Nila; Amirullah, Mulia; Ubaydillah, Muhammad Farhan (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2024)
This research highlights the constraints, solutions, and strategies for optimizing the collection of trade-based zakat in Kota Banjar through the Analytic Network Process (ANP) approach. The research methodology employs ANP as the primary method, which involves identifying criteria and alternatives, constructing a hierarchy through pairwise assessments, calculating global priorities, sensitivity analysis, and interpreting results. Seven contributors participated in the study, consisting of three trade practitioners (Baznas Kota Banjar, Lazismu Kota Banjar, and LAZ Persis Kota Banjar), two experts from zakat observers (MES Kota Banjar, and an academic from STEI Ar-Risalah Ciamis), and two entrepreneurs in Kota Banjar. The study's findings identify priority issues such as trader attitudes, the governance of Zakat Management Organizations (OPZ), and the awareness level of muzak. Crucial steps include improving trader attitudes, OPZ governance, and muzakki awareness. The use of ANP as an analytical approach clarifies the hierarchy of issues and facilitates more targeted decision-making for OPZ in Kota Banjar. The research elaborates on the findings related to eight priority strategies: socialization and education, evaluation and monitoring, ease of paying zakat,involvement of influential figures, regulations, transparency and accountability, program benefits, and recognition or rewards. The implications of this study encourage OPZ in Kota Banjar to enhance socialization through social media and collaboration with community figures, improve governance through regular audits, develop digital zakat payment options, and maintain conventional payment methods.